2011
DOI: 10.1245/s10434-011-2031-6
|View full text |Cite
|
Sign up to set email alerts
|

The Additional Value of Lymphatic Mapping with Routine SPECT/CT in Unselected Patients with Clinically Localized Melanoma

Abstract: SPECT/CT provided relevant additional information in 16 (46%) of the 35 patients. Routine use of SPECT/CT in addition to conventional lymphoscintigraphy is recommended in melanoma patients undergoing lymphatic mapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…The lower-than-reported (10) adjustment rate in breast cancer patients may be explained by the fact that internal mammary and other extraaxillary SNs were not excised routinely in all centers. The global melanoma adjustment rate agrees with previous study results (19,26,29), together with the finding of the greatest benefit for patients with head and neck (30) and trunk (26) locations. This is not surprising because prediction of the lymphatic drainage pathways of melanoma of the head and neck is difficult in a region with more than 350 small lymph nodes and fast tracer uptake (31).…”
Section: Discussionsupporting
confidence: 91%
“…The lower-than-reported (10) adjustment rate in breast cancer patients may be explained by the fact that internal mammary and other extraaxillary SNs were not excised routinely in all centers. The global melanoma adjustment rate agrees with previous study results (19,26,29), together with the finding of the greatest benefit for patients with head and neck (30) and trunk (26) locations. This is not surprising because prediction of the lymphatic drainage pathways of melanoma of the head and neck is difficult in a region with more than 350 small lymph nodes and fast tracer uptake (31).…”
Section: Discussionsupporting
confidence: 91%
“…In another study, concerning 18 melanoma patients, a visualisation rate of 100 % was found for SPECT/CT versus 89 % for planar lymphoscintigraphy; furthermore, SPECT/CT also provided additional anatomical information leading to an adjustment of the surgical approach in four patients [5]. These findings were confirmed in another series including 35 melanoma patients; SPECT/ CT detected additional SNs in seven of them and contributed to modify the surgical approach in ten [6]. More recently, SPECT/CT and planar lymphoscintigraphy detected SNs in 32 patients, both techniques having a visualisation rate of 97 %; however, SPECT/CT contributed to the decision to adjust the surgical approach in 12 patients [7].…”
Section: Cutaneous Melanomamentioning
confidence: 78%
“…Preoperative SPECT/CT imaging has been shown to make intraoperative SN biopsy procedure in melanoma patients easier [10,11], with significantly more SNs detected [12] as well as patient benefit [13]. In this context, intraoperative technologies that exploit the 3D SPECT/CT information may increase its value even further.…”
Section: Discussionmentioning
confidence: 99%